Contribution of problem drug users' deaths to excess mortality in Scotland: secondary analysis of cohort study. (22nd July 2008) - Bloor, Michael; Gannon, Maria; Hay, Gordon; Jackson, Graham; Leyland, Alastair H; McKeganey, Neil
Abstract : Objectives To examine the "Scottish effect"—namely, the growing divergence between mortality in Scotland and England that is not explained by national differences in levels of deprivation—and, more specifically, to examine the extent to which the Scottish effect is explained by cross national differences in the prevalence of problem drug use. Design Secondary analysis of cohort study (the DORIS study). Participants 1033 Scottish drug users recruited to the cohort study in 33 drug treatment facilities across Scotland in 2001-2 and followed up 33 months later in 2004-5. Results 38 deaths occurred in the cohort, giving a standardised mortality ratio for the cohort of 1244 (95% credible interval 876 to 1678). Only 22 of the 38 deaths in drug users were classified as drug related deaths. From estimates of the size of the problem drug using populations in both England and Scotland, the contribution of deaths in drug users to national death rates can be estimated: the attributable risk fraction for Scotland is 17.3% (12.3% to 22.8%) and that for England is 11.1% (7.8% to 14.8%). Excluding estimated numbers of deaths in drug users would bring down age standardised mortality at ages 15-54 years from 196 to 162 per 100 000 in Scotland and from 138 to 122 per 100 000 in England; 32.0% (22.3% to 43.0%) of the excess mortality in Scotland is due to drug use. Conclusion Although problem drug use is a low prevalence risk behaviour, it carries a high mortality; the standardised mortality ratio for Scottish drug users is 12 times as high as for the general population. The higher prevalence of problem drug use in Scotland than in England accounts for a third of Scotland's excess mortality over England. Successful public health efforts to reduce the prevalence of problem drug use in Scotland or deaths in Scottish drug users would have a dramatic impact on overall mortality in Scotland.